Hubungan Antara Tingkat Kemandirian Dengan Self-Adjustment Pada Mahasiswa Rantau - Adilla Putri Nur Afifah; Wahyu Endang Setyowati; Betie Febriana (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the relationship between independence and self-adjustment among migrant students of the Faculty of Health, Universitas Islam Sultan Agung (UNISSULA), Semarang. Using a quantitative cross-sectional design, data were collected from 200 migrant students selected through total sampling from a population of 719 students. Two standardized questionnaires measuring independence and self-adjustment were administered online and had passed validity and reliability testing. Data analysis employed descriptive statistics and Pearson Product Moment correlation. The results indicate a positive and significant relationship between independence and self-adjustment (r = 0.502; p < 0.001), showing that higher levels of independence are consistently associated with better adjustment to academic and social environments. Independence contributes to emotional regulation, identity development, social integration, and professional readiness among students. These findings highlight the strategic role of independence as a core psychological resource in supporting successful adaptation during the transition to higher education. The study recommends strengthening independence through orientation programs, counseling services, and student development policies to enhance well-being, resilience, and academic success among migrant students.